A cross sectional study in cognitive and neurobehavioral impairment in long-term nasopharyngeal cancer survivors treated with intensity-modulated radiotherapy. (February 2019) - McDowell, Lachlan J.; Ringash, Jolie; Xu, Wei; Chan, Biu; Lu, Lin; Waldron, John; Rock, Kathy; So, Nathaniel; Huang, Shao Hui; Giuliani, Meredith; Hope, Andrew; O'Sullivan, Brian; et al.
Highlights: NPC survivors treated with IMRT demonstrate moderate rates of neurocognitive impairment. Observed patient and family reported neurobehavioral dysfunction in this cohort was high. Further work is needed to reduce neurocognitive and neurobehavioral dysfunction is needed. Abstract: Purpose/objectives: To determine neurocognitive and neurobehavioral impairment in long-term nasopharyngeal cancer survivors (NPC) treated with intensity-modulated radiotherapy (IMRT). Materials/methods: A cross-sectional cohort of NPC ≥4 years (y) following IMRT was assessed. Objective cognitive function was measured using the Montreal Cognitive Assessment (MoCA) and patient-reported memory was assessed with the MDASI-HN problems remembering item. Patient and family ratings of patients' neurobehavioral symptoms of apathy, disinhibition and executive dysfunction were assessed with the Frontal Systems Behavior Scale (FrSBe). Other patient-reported symptoms (MDASI-HN), mood (HADS), and quality of life (FACT-H&N) were also collected. Results: Among 102 participants: M:F = 66:36; median age 56y (32–77); median time since IMRT 7.5y (4.2–11.1). Impaired MoCA scores (<23) were observed in 33 (32%). Patient and family ratings of pre-illness neurobehavioral symptoms were in the normal range (total FrSBe T-scores 53.3 and 59.0 respectively). In contrast, post-treatment patient and family T-scores were clinically impaired (64.7, 71.3 respectively), with apathy, disinhibition and executive dysfunction post-treatment ratings all significantly worse than pre-treatment ( p  < 0.001). Prevalence of clinically significant post-treatment disturbance was high by patient and family ratings (48%/66% apathy, 35%/53% disinhibition, 39%/56% executive dysfunction). Post-treatment neurobehavioral symptoms strongly correlated with lower quality of life ( r  = −0.62) and higher anxiety ( r  = 0.62) and depression scores ( r  = 0.67, all p  < 0.001). Total MoCA scores did not correlate with RT dose. However, greater declines in apathy, disinhibition and executive dysfunction were associated with receiving >75 Gy to temporal lobes. Conclusion: NPC treated with IMRT had moderate to high rates of neurocognitive impairment and clinically significant apathy, disinhibition, and executive dysfunction.